2019
DOI: 10.1002/jcb.29571
|View full text |Cite
|
Sign up to set email alerts
|

CD34 cells in somatic, regenerative and cancer stem cells: Developmental biology, cell therapy, and omics big data perspective

Abstract: The transmembrane phosphoglycoprotein protein CD34 has conventionally been regarded as a marker for hematopoietic progenitors. Its expression on these cells has been leveraged for cell therapy applications in various hematological disorders. More recently, the expression of CD34 has also been reported on cells of nonhematopoietic origin. The list includes somatic cells such as endothelial cells, fibrocytes and interstitial cells and regenerative stem cells such as corneal keratocytes, muscle satellite cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 115 publications
(123 reference statements)
3
25
0
Order By: Relevance
“…post-transcriptional or post-translational regulatory mechanism (Kraan et al, 2014;Picarda et al, 2016;Kapoor et al, 2020). Our study confirmed that the expression of CD34 was positively correlated with FTO expression, while the expression of CD276 was positively correlated with the expression of ALKBH5.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…post-transcriptional or post-translational regulatory mechanism (Kraan et al, 2014;Picarda et al, 2016;Kapoor et al, 2020). Our study confirmed that the expression of CD34 was positively correlated with FTO expression, while the expression of CD276 was positively correlated with the expression of ALKBH5.…”
Section: Discussionsupporting
confidence: 80%
“…The ligand of CD276 and its immunomodulatory effect have not been fully determined ( Stodden et al, 2008 ). Although CD34/CD276 is widely expressed in mRNA in CRC, the expression of the protein is limited in steady-state, which indicates that there is an important post-transcriptional or post-translational regulatory mechanism ( Kraan et al, 2014 ; Picarda et al, 2016 ; Kapoor et al, 2020 ). Our study confirmed that the expression of CD34 was positively correlated with FTO expression, while the expression of CD276 was positively correlated with the expression of ALKBH5.…”
Section: Discussionmentioning
confidence: 99%
“…Ganeshan B. and colleagues, in a previous study on NSCLC 11 , showed how the texture feature MPP has strong correlation with a peculiar characteristic of the tumor detected by the staining with pimonidazole, an exogenous marker of hypoxia. Moreover, MPP also correlates inversely with tumor CD34 expression which is a marker of angiogenesis expressed both on hematopoietic and somatic cells 28 . Similar results were also confirmed by another interesting study performed by Hayano K. and colleagues where Authors assessed the performance of predicting survival with TA in patients with NSCLC treated with antiangiogenetic chemotherapy and assessed with both CT and PET/CT 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, CD34 has been detected at the transcript level in several cancers, including but not limited to renal, thyroid, breast and stomach cancer. However, at the protein level, CD34 is detected in fewer cancer types such as colorectal, thyroid and melanoma (Kapoor et al, 2019), and this condition may be similar in animals, which could be another explanation for the findings. CD34 + has been correlated…”
Section: Discussionmentioning
confidence: 82%